2019
DOI: 10.1111/ene.14035
|View full text |Cite
|
Sign up to set email alerts
|

Early changes in tests of peripheral nerve function during oxaliplatin treatment and their correlation with chemotherapy‐induced polyneuropathy symptoms and signs

Abstract: Background and purpose Assessment of the severity of chronic peripheral neuropathy during oxaliplatin treatment is based on symptoms. Efforts to adjust the total dose of oxaliplatin to prevent severe neuropathy can be complicated by the worsening of neuropathy symptoms following treatment. Objective measures of the structure and function of peripheral nerves during early phases of treatment may aid in determining the optimal oxaliplatin dose in individual patients. Intraepidermal nerve fibre density (IENFD) ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…Finally, patients’ initial (pre-treatment) peripheral neurological function and lifestyle, variables not studied here, may have affected the evaluation of CIPN. Further studies are needed to determine the correlation between initial peripheral neurological function, lifestyle, and CIPN [ 48 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Finally, patients’ initial (pre-treatment) peripheral neurological function and lifestyle, variables not studied here, may have affected the evaluation of CIPN. Further studies are needed to determine the correlation between initial peripheral neurological function, lifestyle, and CIPN [ 48 ].…”
Section: Limitationsmentioning
confidence: 99%
“…Several longitudinal studies, including NCS during OXA therapy, have showed a significant progressive decrease in sensory nerve action potentials (SNAPs) and preservation of motor action compound (CMAPs), in keeping with the presence of an axonal sensory neuropathy, and consistent with the clinical symptoms and signs worsening during the treatment [ 17 , 41 , 58 , 59 , 60 , 61 , 62 , 63 , 64 ]. NCS are capable of objectively assessing the extent of peripheral nerve damage and may also facilitate the identification of patients that manifest subclinical peripheral neuropathy prior to the onset of clinically significant neurotoxicity.…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 85%
“…After sensory examination, reductions in upper and lower limb SNAPs of patients were the most sensitive early markers of neuropathy observed in 40% [ 69 ]. In this line, in one prospective study including 60 gastrointestinal cancer patients, sural nerve velocity and SNAP revealed a significant decrease after 50% and 100% of the planned dose, respectively [ 60 ].…”
Section: Neurophysiological and Device-dependent Predictorsmentioning
confidence: 99%
See 2 more Smart Citations